Electronic reconstruction on dimerized IrTe2. (5th February 2018) - Lee, Hwangho; Ko, Kyung-Tae; Kim, Kyoo; Park, Byeong-Gyu; Yang, Junjie; Cheong, Sang-Wook; Park, Jae-Hoon
Abstract: We investigated the electronic reconstruction in IrTe2 across the charge order phase transition using the angle-resolved photoemission spectroscopy and the ab initio calculation. The complicated shadow bands are attributed to the band folding effect of the charge ordered unit cell, while the valence transition causes the Fermi level shift as well as the size change of the Fermi surface. Implementation of a band unfolding scheme enables us to resolve the complicated folded band features, and successfully provides us information on the electronic reconstruction involving the transition. As a result, we could identify a flattened band and a segmented dispersion near the Γ and A point. We also identified the surface state contributions of additional bands crossing the Fermi level and a Dirac-cone–like band. The observed electronic reconstruction implies that the transition is induced by the strong correlation between the itinerant electrons and the spin-orbit coupled charge ordered states.